(untitled) (Higher Education Politics and Economics, 2023)
There is social and collaborative value in a diverse student body, faculty, and staff. Despite this, universities are slow to establish evidence-based fiscal initiatives to increase representation and retention. We review inequitable financial practices in American higher education, including in endowments, tuition and annual giving, athletics, and research and innovation. We discuss fiscal initiatives that promote diversity, equity, justice, and inclusion (DEJI) while maintaining or increasing return on investment. Historical inequities are discussed in the context of institutional standards and methods of restructuring for DEJI success. A case-study of two Very High Research Activity Institutions in Alabama is used to demonstrate areas of improvement. Restructuring for a equitable, fiscally-responsible, sustainable university system is feasible but requires changes to current standards.